An Overview of Dual Targeting Nanostructured Lipid Carriers for the Treatment of Ovarian Cancer - Rajendra, Praharsh Kumar Mandadhi; Jawahar, Natarajan; Raman, Rajeshkumar; Shivakumar, Hagalavadi Nanjappa; Balan, Anjali Puthusserikkunnu (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: To summarize main findings from research on oral delivery of Nanostructured lipid carriers targeting ovarian cancer. Methods: A narrative review of all the relevant papers known to author was conducted. Results: Ovarian cancer is one of the most common gynaecologic cancer, the frontline treatments for which are surgical approach followed by radiotherapy or chemotherapy. Chemotherapy has its own limitations; consequently, there is a need to develop a targeted drug delivery system with high efficacy. Preclinical evidence suggests that combination therapies are likely to be effective in ovarian cancer. However, from clinical reports, it is evident that chemotherapeutic drugs have lower therapeutic value for the treatment of ovarian cancer. We propose that these limitations can be overcome by a novel formulation consisting of nanostructured lipid carriers. Recent pharmacological research has successfully potentiated the effects of combination therapy in acute animal preparations by inhibiting proteins that are involved in different physiological pathways of cancer cells. Conclusion: We have reviewed the scope of nanostructured lipid carriers concerning chemotherapy of ovarian cancer. The advantages of oral administration of these lipid carriers are discussed. Also, the various nano-lipid formulations and combination therapies reported along with their therapeutic outcomes have been reviewed. In light of this, nanostructured lipid carriers containing two different active ingredients for oral administration could be a potential approach for the effective treatment of ovarian cancer.
Keywords: Ovarian cancer; Nanostructured lipid carriers; Dual targeting; Chemotherapy; Oral delivery